Not Welcome A Critical Analysis of Ableism in Canadian Immigration Policy from 1869 to 2011 - Wong, Edward Hon-Sing (Critical Disability Discourses, 2012)
A Foucauldian discourse analysis of Canadian immigration policies and state practices reveals the ableist foundations of the Canadian nation-state. Throughout much of Canadian history, people with disabilities have been excluded through the immigration system. People with disabilities are often times prohibited from obtaining legal status, and even when status is obtained, it is often marked with precariousness. In order to contextualize ableism in the immigration system, I argue that borders are socially constructed, serving to segregate the labour market and to create precarious circumstances for workers in the contexts of capitalism and neoliberalism. These foundations of the Canadian immigration system, which have existed throughout Canada’s history and can be seen in today’s policies, serve to pathologize, playing a major role in the marking of bodies as disabled. Furthermore, immigration policies construct people with disabilities as societal burdens who are unable to contribute to the community. Keywords: Ableism, immigration, racism, deportation, excessive demand, pathologization